Pengaruh Brand Equity Terhadap Consumer Satisfaction Di Restoran Sushi Tei Jakarta Selatan - Sri Wulandari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to examine the effects of physical quality, staff behavior, brand identification and lifestyle on the satisfaction of Sushi tei restaurant consumers in Jakarta. This research was conducted by spreading questionnaires to 150 respondents who are all Sushi tei consumers in Jakarta. The result data of the next questionnaire is processed by using regression analysis technique which its processing will be done with the help of SPSS program. The result of analysis shows that physical quality variable, staff behavior, brand identification and lifestyle either partially or simultaneously have a positive and significant effect on the satisfaction of Sushi tei consumer in restaurant Jakarta. Furthermore, the result of analysis shows that physical quality, staff behavior, brand identification and lifestyle simultaneously affect the satisfaction of Sushi tei consumer in South Jakarta with contribution of 73,7%.